The potential effect of neurobiological evidence on the adjudication of criminal responsibility of psychopathic defendants in involuntary manslaughter cases - Berryessa, Colleen M. (Psychology, crime & law, 2021)
Research on how neurobiological evidence influences jurors’ decision-making in adjudications of criminal responsibility is growing. Mock trial studies on this topic have almost entirely considered purposeful violent crimes, but the results of these studies are inconsistent. The present study tests the effects of neurobiological evidence (neuroimaging, clinical psychology, and genetics) on outcomes related to criminal responsibility for psychopathic defendants by using a unique and novel crime paradigm: involuntary manslaughter, committed either through recklessness or negligence. Dependent variables were guilt, legal insanity, and beliefs about the defendant’s free will at the time of the crime. We found no evidence that neurobiological evidence affected mock jurors’ verdicts of guilt or legal insanity, but, interestingly, we found that neuroimaging evidence significantly influenced mock jurors’ perceptions of the defendant’s free will. Additionally, mock jurors with higher self-reported psychopathy scores rated defendants as significantly guiltier when presented with reckless conduct and as having significantly less free will when presented with neuroimaging evidence on psychopathy. Our findings add to a growing body of research suggesting that neurobiological evidence appears to have only minor influences on jurors’ decision-making.